ANALISIS PENGENDALIAN PERSEDIAAN SHEET SPHC DENGAN METODE MIN-MAX STOCK DI PT. INDOTEHNIK CIPTA SEMBADA - Adi Candra; Sofian Bastuti; Muhamad Abdul Furqon (Industrika : Jurnal Ilmiah Teknik Industri, 2022)
Indotehnik Cipta Sembada is a manufacturing company engaged in the design & construction of the Panel Maker electrical system. In an electrical panel, Sheet SPHC (Steel Plate Hotrolled Coiled) is used as the basic material for making box panels. In determining the SPHC Sheet inventory, the company is still based on previous experience, causing frequent stock outs. To help solve the problem of planning raw material requirements, the application of the Min-Max Stock method will assist in meeting the supply of raw materials so that there is no stock out. From this research, it was found that the Safety Stock for 1.5mm SPHC Sheet is 131 sheets and for 2.0mm SPHC Sheet is 151 sheets, the Minimum Stock limit for 1.5mm SPHC Sheet is 106 sheets and for 2.0mm SPHC Sheet is 122 sheets, and the Maximum Stock limit for 1.5mm SPHC Sheets is 213 sheets and for 2.0mm SPHC Sheets is 237 sheets. In addition, in using the Min-Max Stock method the company can save inventory costs, from the calculation results for 1.5mm SPHC Sheet the company can save Rp.2,061,589 and for 2.0mm SheetSPHC Rp.3,240,392. Keywords: Inventory, EOQ, Min-Max Stock